Adoption and profitability of Binadhan-16 in some selected areas of Bangladesh - Sultana, R; Rahman, R H; Sarkar, M M A; Haque, M R; Islam, S (Bangladesh Journal of Nuclear Agriculture, 2025)
The study was conducted in three Binadhan-16 growing areas of Bangladesh, namely Mymensingh, Netrokona and Rangpur districts. The objectives of the study were to find out the determinants of adoption of Binadhan-16 rice variety at the farm level and to estimate the costs and return of Binadhan-16 cultivation in the study areas. Moreover, some problems of the Binadhan-16 cultivation were also investigated in this study. This study was based on primary data which were collected from 180 farmers, 60 from each district where 30 was adopter and 30 was non-adopter of Binadhan-16 growers. Data were collected through face to face interview with the help of a pre-designed interview schedule from three upazillas i e. Valuka (Mymensingh), Purbadhala (Netrokona) and Sadar (Rangpur). Descriptive statistics and logit regression model were used to fulfill the objectives. The result of logit regression model shows that farm size, yield, seed, training and extension contact have positive and significant effect on Binadhan-16 adoption. Education and cultivation duration were found as negatively significant variables in explaining the variation in Binadhan-16 adoption. The study also found that total variable cost of Binadhan-16 cultivation was Tk. 44346 per hectare which was 66.78% of total cost of production. The highest cost item was human labour which accounted for 46.44 % of the total cost. Cost of land preparation was 17.84% and land use cost accounted for 14.63% of total cost and ranked as second and third cost items, respectively. On an average, the total cost of production was Tk. 66404 per hectare where 33.22% was fixed costs and 66.78% was variable cost. It was found that Binadhan-16 production is profitable. The highest yield was found at Rangpur (5546 kg ha-1) followed by Mymensingh (5379 kg ha-1) and Netrokona (5297 kg ha-1). The average selling price of Binadhan-16 was Tk. 24.88 kg-1 where cost of production was Tk. 12.28 kg-1. The average gross margin was found Tk. 98756 on variable cost basis. The average net return per hectare was Tk. 76698. The average Benefit Cost Ratio (BCR) was 2.16. Regarding major problems of the variety cultivation, 15% mentioned about high labour cost which ranked top followed by quality seed in timely manner (14%), infestation of disease (11%), scarcity of labour (9%), low price of paddy and high transportation cost (8%). As the variety yield higher profit more emphasis should be given on farm size, seed, yield, and training programme for the expansion of the variety. Bangladesh J. Nuclear Agric, 38(2): 125-135, 2024